Multi-domain optimization of high power-density PM electrical machines for system architecture selection - Golovanov, Dmitry; Papini, Luca; Gerada, David; Xu, Zeyuan; Gerada, C. (Institute of Electrical and Electronics Engineers, 2017)
The power density of electrical machines for transport applications has become a critical aspect and target of optimization. This paper looks at the development of an intelligent, rapid, flexible, and multidomain tool to aid for system-level optimization of electrical machines within next-generation high power density applications. The electromagnetic, thermal, and mechanical aspects are wholly integrated, thus enabling the optimization including the nonactive mass. The implementation and overall architecture of the tool are described, and using a case study drawn fromthe aerospace industry, the tool is used to compare the power density of various surface permanentmagnet topologies including single airgap and dual airgapmachines, highlighting the particular suitability of the dual rotor topology in achieving the best power to mass ratio. Finally, the accuracy of the tool is highlighted by practical realization and experimental validation.